Capturing the buzz: social media as a design informant for urban civic spaces - Loring, Mitchel Lee (Kansas State University, 2014)
BACKGROUND AND PURPOSE: Civic spaces are important nodes of community life. Especially in an urban context, civic spaces provide a necessary place that people can gather for events, meet others, and experience openness in an otherwise crowded environment. However, not all civic spaces are successful in providing these opportunities to city dwellers. Washington Square in Kansas City, Missouri is one such civic space that is currently underused and unsuccessful. Traditional methods of analyzing public spaces can be supplemented by a social media-based methodology of analysis. Analyzing social media posts submitted within the geographic boundaries of a civic space offers rich insights into the public perception and usage of these places. The application of a social media-based methodology to Washington Square results in the development of solutions for addressing this space’s dilemmas and Kansas City’s goals for the area. METHODS: Instagram and Twitter posts are collected within the geographic boundaries of Washington Square and three other civic spaces—which have been identified as exhibiting characteristics of Kansas City’s goals for Washington Square. Using thematic coding, geographic analysis, and textual analysis, these posts are analyzed to discover how people are using and perceiving these civic spaces. This data is synthesized to create solutions for the redevelopment of Washington Square. FINDINGS & CONCLUSION: This research demonstrates that a social media-based analysis can effectively inform planners and designers of the ways in which people use and perceive civic spaces. The application of this methodology to Washington Square has led to the creation of nine solutions. These solutions aim to improve Washington Square’s functionality, its identity, and its interaction with the surrounding urban environment.
Keywords: Social media; Urban design; Public spaces; Urban planning; Twitter; Instagram; Area Planning and Development (0341); Landscape Architecture (0390); Urban Planning (0999)